CFD studies on triangular micro-vortex generators in flow control - Yashodhar, V.; Humrutha, G.; Kaushik, M.; Khan, Sher Afghan (IOP Publishing, 2017)
In the present study, the flow characteristics of the commercially used S809 wind turbine airfoil controlled with triangular counter-rotating micro-vortex generators at stall angle of attack of 15 degrees and 10 m/s, 15 m/s and 20 m/s (speed range used in the wind turbine applications) had been computationally investigated. In addition to the controlled airfoil, an uncontrolled airfoil was also studied for the comparison. The modelling and analysis had been carried out using incompressible, Reynolds Averaged Navier Stokes equation using Spalart-Allmaras one equation turbulence model. The numerical computations were performed with SIMPLE algorithm. The velocity profiles at different locations on the suction surface were plotted for both uncontrolled and controlled airfoils. The shear stresses exerted on the upper surface of the airfoil in both the configurations were also compared. It is found that the controlled airfoil, the shear stress distribution was greatly increased near to trailing edge of the airfoil revealing the superiority of vortex generators in increasing the efficiency of wind turbine by delaying boundary layer separation. The qualitative results of flow visualization in the spanwise direction also support the quantitative findings of velocity profiles and shear stress distribution.